Epitope mapping of Anti-YB-1 antibodies using truncated proteins - Wei, T.C.; Shamsuddin, S. (Penerbit Universiti Kebangsaan Malaysia, 2014)
Increased expression and nuclear localization of Y-box-binding protein-1 (YB-1) are associated with drug resistance and tumor progression. Detection of YB-1 primarily depends on the recognition of YB-1 antibody on its epitopes. To determine the epitopes binding of anti-YB-1 A-16 and 59-Q antibodies, three YB-1 truncated proteins were generated using bacterial expression system and their aberrant migration were reported. Epitope mapping analyses revealed anti-YB-1 A-16 antibody recognized epitope at 1-127 amino acid residues of YB-1, whereas 59-Q antibody was reactive with epitope at 61-127 amino acid residues. Based on our findings, 59-Q antibody was suggested used in the future study to avoid ambiguity.